The influence of games on the development of speaking skills in students of eighth-year at Unidad Educativa Baltasara Calderón de Rocafuerte - Ramírez Pazmiño, Allison Andrea (2015)
In teaching a foreign language, it is essential to provide students with the opportunity of having an oral communication in order to help students learning English when they are put into real-life situations on the game-like activities in which the learners interact at the moment of speaking. Games help as an important tool to practice the language learning. At the same time, the communicative competence can help a lot. Games also give to the students the opportunity to express the language what they have learned. The private school, “Unidad Educativa Baltasara Calderon de Rocafuerte,” located in the south of Guayaquil gave us the appropriate conditions to analyze through a qualitative research, the students’ reaction to the implementation of the games in class, and the influence of certain activities in the students……